Case report: Multimodality imaging of unusual coronary to pulmonary collaterals in chronic thromboembolic pulmonary hypertension - Goyal, Ansh; Avery, Ryan; Cuttica, Michael J.; Flaherty, James D.; Malaisrie, S. Chris; Mylvaganam, Ruben (Frontiers in Cardiovascular Medicine, 2023)
We present unusual coronary-pulmonary collaterals in a 65-year-old with unilateral CTEPH. Perfusion mapping of a dual-energy computed tomography (DECT) study revealed areas of right lung that were minimally perfused despite unilateral occlusion of the right pulmonary artery, leading to the discovery of coronary-pulmonary collaterals via invasive coronary angiography. Pulmonary thromboendarterectomy removed the clot en-bloc. Post-surgery DECT and catheterization confirmed restoration of pulmonary arterial circulation and excellent hemodynamic response. Here, significant perfusion to a unilaterally proximally obstructed lung with DECT was revealed, hastening the discovery of rarely documented coronary-pulmonary artery collaterals.